Structural models for spreading and scaling digital health initiatives: A scoping review protocol - Celia Laur; Karen Lee; Andrew Milat; Samuel Petrie; Zeenat Ladak; Vincci Lui; Alix Hall; Nicole Nathan; Priscilla Medeiros; Noah Ivers; Onil Bhattacharyya (PLoS ONE, 2026)
Background Healthcare initiatives have a larger impact if effective initiatives are spread (brought from one site to the next) or scaled (infrastructure developed to underpin and support widespread implementation), while sustaining initial benefits. Unfortunately, many initiatives, including digital health initiatives, remain confined to the pilot stage. Of those initiatives that do progress, little is known about how to plan for the equitable spread and scale of effective initiatives. There are many structural “models” of spread and scale, defined here as conceptual representations of how initiatives are organised and delivered across multiple settings (i.e., hub-and-spoke model), yet little is known about these models. Objectives Primary Objective: To identify and describe structural models for spreading and scaling digital health initiatives. Secondary Objectives: 1. To describe the associated factors, strengths, limitations, and necessary preconditions associated with each model. 2. To describe the barriers and facilitators experienced when applying each model. 3. To explore whether and how each model prioritized equitable delivery of care. 4. To determine which pre-established types of scale (horizontal, vertical, diversification, and spontaneous) are associated with each model. Methods A scoping review will be conducted following Joanna Briggs Institute (JBI) methodology and reported in accordance with PRISMA-ScR guidelines. The search strategy includes peer-reviewed databases for health and business, alongside grey literature sources. Eligibility criteria follow the Population-Concept-Context framework, focusing on digital health initiatives delivered in healthcare settings. Results The review will produce a comprehensive overview of structural models for spreading and scaling digital health initiatives, including model names, descriptions, strengths, limitations, preconditions, associated barriers and facilitators of applying each model, relationships between models and established types of scale, and equity considerations. Conclusions This novel review aims to inform practical planning of how to bring digital health initiatives to new settings and populations, to support more equitable access to these initiatives.